The Adjustment of Savings to Investment in a Growing Economy - Meade, J. E. (Review of Economic Studies, 1963)
Journal Article The Adjustment of Savings to Investment in a Growing Economy Get access J. E. Meade J. E. Meade Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 3, October 1963, Pages 151–166, https://doi.org/10.2307/2296315 Published: 01 October 1963